1981
DOI: 10.1038/clpt.1981.125
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil disposition kinetics in chronic atrial fibrillation

Abstract: Verapamil disposition was studied in 12 patients with chronic and fibrillation. After an intravenous bolus of 15 mg plasma concentration was determined and the data fit in a three-compartment model. Model independent parameters were calculated and values for half-life (t 1/2), clearance, and steady-state distribution volume were 6.3 +/- 4 hr, 13.3 +/- 7.7 ml/min/kg, and 4.3 +/- 1.9 l/kg. The model was used to design a multistep infusion scheme, which was employed successfully to achieve predetermined plasma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 0 publications
5
33
0
Order By: Relevance
“…However, chronic administration appears to result in accumulation of the drug to a greater extent than that predicted on the basis of single dose pharmacokinetic data. Kates et al (1981) observed that the mean serum concentration of verapamil was twice that predicted during long-term oral administration in 12 patients with chronic atrial fibrillation. Similar results have been reported in subsequent investigations (Eichelbaum & Somogyi, 1984;Freedman et al, 1981;Shand et al, 1981).…”
Section: Introductionmentioning
confidence: 95%
“…However, chronic administration appears to result in accumulation of the drug to a greater extent than that predicted on the basis of single dose pharmacokinetic data. Kates et al (1981) observed that the mean serum concentration of verapamil was twice that predicted during long-term oral administration in 12 patients with chronic atrial fibrillation. Similar results have been reported in subsequent investigations (Eichelbaum & Somogyi, 1984;Freedman et al, 1981;Shand et al, 1981).…”
Section: Introductionmentioning
confidence: 95%
“…Following intravenous administration, the systemic clearance of verapamil is high and approaches hepatic blood flow. Due to this high hepatic extraction, verapamil undergoes extensive 'first-pass' elimination when given orally and therefore despite its almost complete absorption absolute bioavailability is on average only 20-30% (Schomerus etal., 1976;Eichelbaum et al, , 1981aFreedman et al, 1981;Johnston et al, 1981; Kates et al, 1981;Somogyi etal., 1981;Woodcock etal., 1981a, b;Anderson et al, 1982). The drug preparation available for clinical use is a racemic mixture of the (+)-and (-)-isomer.…”
Section: Introductionmentioning
confidence: 99%
“…doses of 5 to 10 mg. pass metabolism (Schomerus et al, 1976; Eichel-However, oral doses 10 to 15 times greater than baum et Freedman et al, 1981;i.v. doses are usually required to produce Kates et al, 1981;Anderson et al, 1982; comparable clinical effects (Singh et al, 1983). McAllister et al, 1982).…”
Section: Introductionmentioning
confidence: 99%